Local Wisdom Values in the Poems Collection of Ayat Sunyi by Emi Suy as Strengthening Children's Character Education in Indonesia Through Literary Works - Wati, Maulida Laily Kusuma; Supriyanto, Teguh; Doyin, Mukh; Pristiwati, Rahayu (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Character education in Indonesia is currently facing various challenges, especially due to the growing social dynamics influenced by global culture, which tends to overlook local cultural values. In this context, literary works, particularly poetry, play a vital role in conveying messages of local wisdom that deeply influence character development. The poem collection Ayat Sunyi by Emi Suy highlights the importance of values such as cooperation, tolerance, honesty, justice, wisdom, human-nature relations, and religiosity. Using a literary sociology approach and sociological theory, this study reveals that local wisdom values, as part of social morality, are strongly portrayed in the poems. The analysis shows that the poems not only depict harmony between humans and nature but also emphasize the role of women as guardians of cultural values and agrarian spirituality. These poems emphasize the importance of preserving cultural traditions that are now being marginalized, while also educating students to appreciate their culture, value life, and develop responsible character. Thus, the poems serve a significant role in shaping a better young generation by instilling values of local wisdom that nurture individuals to be caring, empathetic, and deeply rooted in national identity. The symbolism of Dewi Sri, the earth, and prayer in the poems provides a strong foundation for reinforcing character education, preparing Indonesia's Golden Generation to become individuals of noble character, empathy, and cultural integrity.